21: Pediatric Post-Traumatic Headaches and Peripheral Nerve Blocks of the Scalp: A Case Series and Satisfaction Survey. Issue 6 (1st June 2014) - Dubrovsky, S; Friedman, D; Kocilowicz, H
Abstract: BACKGROUND: Headaches are the most frequently reported persistent symptoms following a pediatric mild traumatic brain injury (MTBI), may be challenging to treat and can transform into debilitating chronic headaches. The beneficial use of peripheral nerve blocks of the scalp has been reported for adults with post-traumatic headaches. OBJECTIVES: Characterize the therapeutic effect of peripheral nerve blocks of the scalp for children and adolescents with post-traumatic headaches. DESIGN/METHODS: Retrospective case series on all patients <18 years of age treated between January 2012 and June 2013 in the MTBI clinic with a nerve block. The main outcome measure was the proportion of patients with a good therapeutic effect, defined by the duration of the block being >24 h and/or repeat blocks requested. A data extractor blinded to main outcome measures performed the chart review. A patient satisfaction survey also assessed the perceived benefit of the procedure and whether the patients would recommend this treatment to their family and friends. RESULTS: A total of 62 nerve blocks were performed on 28 patients for 30 injuries that led to post-traumatic headaches. The mean age was 14.6 (1.7) years, 80% female, with 77% resulting from a sport-related concussion. The first nerve blocks were performed 70 (54.2) days post-injury; 47% had a single nerve block encounter with a mean number of nerve blocks of 2.1 (1.4) with a range of 1 to 6. A greater occipital nerve block was done on all patients with 73% having other nerves of the scalp blocked as well (supra-orbital and/or lesser occipital). The therapeutic effect was good in 93% of patients with 71% reporting immediate complete relief of their headaches; the mean percent headache reduction was 94%. The satisfaction survey (response rate 82%) revealed a similar trend: 83% recalled immediate relief of their headaches, 83% and 61% indicated that it improved or resolved their headaches in the days to weeks following the injection(s), respectively and 91% would recommend a nerve block for post-traumatic headaches. CONCLUSIONS: The ease with which peripheral nerve blocks of the scalp can be performed combined with the immediate relief experienced by patients makes them a potential addition to the armamentarium of headache management strategies for children and adolescent with post-traumatic headaches.